PENENTUAN PRIORITAS OBJEK WISATA ALAM MENGGUNAKAN PENDEKATAN SPASIAL DI KOTA PADANG - Isman, Mentari Ashari; Syarief, Azhari (JURNAL BUANA, 2024)
The tourism sector has an important role as one of the country's sources of foreign exchange revenue, and can increase national economic growth, especially to reduce unemployment and encourage national productivity. One of the areas that has the most tourist destinations in West Sumatra Province is Padang City. Besides being known as the city of cultural arts, natural tourism is one of the most attractive tourism sectors in Padang City. To support the development of natural tourism objects in Padang City, a special strategy is needed, one of which is to determine tourism development priorities based on aspects of attractions, accessibility, and amenities of each tourist attraction with ADO-ODTWA guidelines. With the scoring method, later the combined total score will be classified into very feasible classes, decent enough and not worthy to be a priority for natural attractions in Padang City.